A Bibliometric Analysis of the Scientific Production and Collaboration between Graduate Programs in Manufacturing Engineering in Brazil - Dutra, Silvana; Lezana, Álvaro; Dutra, Moisés; Pinto, Adilson (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
In Brazil, most of the scientific research is developed within the scope of the Brazilian university Graduate Programs, which host the Master’s and Doctorate courses. These Graduate Programs are evaluated by the Coordination for the Improvement of Higher Education Personnel, an organ of the Brazilian Ministry of Education, which classifies the Graduate Programs in a ranking that ranges from 1 to 7, with 7 being the level of excellence. Among the inputs used by this evaluation process, there are the Brazilian researcher Lattes CVs, which contain all the details of the researchers’ academic life, such as their academic background, areas of professional activity, intellectual production, student supervisions, collaboration networks, etc. The CVs of Brazilian researchers are publicly available for download in XML format. In this paper, we undertake a bibliometric analysis of the CVs taken from researchers who are part of a sample of Brazilian Graduate Programs in Manufacturing Engineering that have national ranking greater or equal to 4. For a period of 10 years (2008-2017), we sought to identify the most published topics, vehicles most used for publication, the basic training of the researchers, and the potential existence of collaboration networks between the Graduate Programs. Among other results, we could identify that 29 institutions are Alma Mater of 68.36% of the researchers analyzed. In addition, it was possible to verify that only two Brazilian scientific events account for 7.5% of the total of publications for the analyzed sample and period. Palavras-chave: Manufacturing Engineering; Bibliometric Analysis; Graduate Programs; Scientific Production; Scientific Collaboration; Brazilian Science. Link: https://periodicos.ufpb.br/ojs2/index.php/ies/article/view/44852